2021
DOI: 10.31234/osf.io/7s8bk
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Using Smiles, Frowns, and Gaze to Attribute Conscious States to Others: Testing Part of the Attention Schema Theory

Abstract: In the attention schema theory, people attribute the property of consciousness to themselves and others because it serves as a schematic model of attention. Most of the existing literature on monitoring the attention of others assumes that people primarily use the gaze direction of others. In that assumption, attention is not represented by a deeper model, but instead limited mainly to a single, externally visible parameter. Here we presented subjects with two cues about the attentional state of a face: direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Even more than gaze tracking, people construct rich and multidimensional models of other people’s attention ( 66 68 ). For example, people combine facial expression cues with gaze cues to reconstruct the attentional states of others ( 69 ). People also intuitively understand whether someone else’s attention is exogenously captured or endogenously directed ( 66 , 67 ).…”
Section: Evidence Of An Attention Schemamentioning
confidence: 99%
“…Even more than gaze tracking, people construct rich and multidimensional models of other people’s attention ( 66 68 ). For example, people combine facial expression cues with gaze cues to reconstruct the attentional states of others ( 69 ). People also intuitively understand whether someone else’s attention is exogenously captured or endogenously directed ( 66 , 67 ).…”
Section: Evidence Of An Attention Schemamentioning
confidence: 99%
“…Recently, however, it has been suggested that reconstructing the attention of others may involve a process much deeper than using a single cue (the direction that someone’s eyes are pointing) to infer the momentary attention state. It may involve using multiple cues to build a rich, predictive model of the other person’s attention, or an “attention schema” ( 18 23 ). The hypothesis differs from prior conceptualizations in two main ways.…”
mentioning
confidence: 99%